Personal satisfaction of women and life time administrative workers National University Huancavelica. - Capcha Huamaní , Arnaldo Virgilio (2020)
OBJECTIVE: Was performed in order to determine the relationship between women’s personal satisfaction and life time Administrative workers National University of Huancavelica. METHODS: Used was correlational, not experimental design used. It was considered as a study area of Huancavelica National University, the study population was women workers in the National University of Huancavelica, the sample was non- probabilistic and the sample was living census or why it took the total population it was in a number of 53 workers.The method that was employed was: the survey by interview guide instrument.RESULTS:Were 43.4% (23) of workers are satisfied of which, 30.2 (16) 0.4% are young adults, while 9.4% (5) are mature adults and only 3.8% (2) they are older. On the other hand we have a 30.2% (16) of workers shortly satisfied which 22.6%(6) are young adults and only 7.5% (4) correspond to mature adult, not having any little satisfied elderly. Finally we can say thar 26.4% (14) of workers are dissastisfied, of which 20.8% (11) corresponds to young adults and only 5.7% (3) are older. CONCLUSION: That the correlation between women’s personal satisfaction and life time Administrative workers of the National University of Huancavelica, as evidenced by the statistical test pearson correlation coefficient (Pearson r) (4,546) accepting the research hypothesis and reject the null hypothesis.